Survei Tingkat Kesegaran Jasmani Siswa Kelas VIII SMPN 1 Pademawu Pamekasan - Apriyadi, Rian Bahtiar; Handayani, Heni Yuli; Purwoto, Septyaningrum Putri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study concludes that the physical fitness level of grade VIII students at SMPN 1 Pademawu Pamekasan is overall in the "Poor" category. The participants in this study were 112 students from grade VIII at SMPN 1 Pademawu Pamekasan, consisting of 59 male students (52.68%) and 53 female students (47.32%) , all of whom were 13 years old. The research method used was descriptive quantitative with a one-shot model approach. The instrument used was the multi-stage fitness test (beep test) to measure the students' physical fitness level, specifically their aerobic capacity or cardiorespiratory endurance. Data analysis was performed using quantitative descriptive analysis, which involved calculating the frequency and percentage of the test results categorized into four levels of physical fitness: Good, Sufficient, Poor, and Very Poor. The survey results show that the physical fitness level of male students can be significantly categorized as "Sufficient". Of the 59 male students, 28.81% (17 students) were in the "Good" category , 37.29% (22 students) "Sufficient" , 25.42% (15 students) "Poor" , and 8.48% (5 students) "Very Poor". Meanwhile, the physical fitness level of female students can be significantly categorized as "Poor". Of the 53 female students, 26.42% (14 students) were in the "Sufficient" category , 64.15% (34 students) "Poor" , and 9.43% (5 students) "Very Poor".